New Zealand blackcurrant extract improves cycling performance and fat oxidation in cyclists - Cook, M. D.; Myers, S. D.; Blacker, S. D.; Willems, M. E. T. (European Journal of Applied Physiology, 2015)
Purpose: Blackcurrant intake increases peripheral blood flow in humans, potentially by anthocyanin-induced vasodilation which may affect substrate delivery and exercise performance. We examined the effects of New Zealand blackcurrant (NZBC) extract on substrate oxidation, cycling time-trial performance and plasma lactate responses following the time-trial in trained cyclists. Methods: Using a randomized, double-blind, crossover design, 14 healthy men (age: 38 ± 13 years, height: 178 ± 4 cm, body mass: 77 ± 9 kg, VO2max: 53 ± 6 mL/kg.min, mean ± SD) ingested NZBC extract (300 mg/day CurraNZ™ containing 105 mg anthocyanin) or placebo (PL, 300 mg microcrystalline cellulose M102) for 7 days (washout 14 days). On day 7, participants performed 30 min of cycling (3 × 10 min at 45, 55 and 65 % VO2max), followed by a 16.1 km time-trial with lactate sampling during a 20-min passive recovery. Results: NZBC extract increased fat oxidation at 65 % VO2max by 27 % (P < 0.05) and improved 16.1 km time-trial performance by 2.4 % (NZBC: 1678 ± 108 s, PL: 1722 ± 131 s, P < 0.05). Plasma lactate was higher with NZBC extract immediately following the time-trial (NZBC: 7.06 ± 1.73 mmol/L, PL: 5.92 ± 1.58 mmol/L, P < 0.01). Conclusions: Seven-day intake of New Zealand blackcurrant extract improves 16.1 km cycling time-trial performance and increases fat oxidation during moderate intensity cycling.